Naphthalonitriles featuring efficient emission in solution and in the solid state - Thulaseedharan Nair Sailaja, Sidharth; Maisuls, Iván; Kösters, Jutta; Hepp, Alexander; Faust, Andreas; Voskuhl, Jens; Strassert, Cristian A. (Beilstein Journal of Organic Chemistry, 2020)
In this work, a series of γ-substituted diphenylnaphthalonitriles were synthesized and characterized. They show efficient emission in solution and in the aggregated state and their environment responsiveness is based on having variable substituents at the para-position of the two phenyl moieties. The excited state properties were fully investigated in tetrahydrofuran (THF) solutions and in THF/H2O mixtures. The size of the aggregates in aqueous media were measured by dynamic light scattering (DLS). The steady-state and time-resolved photoluminescence spectroscopy studies revealed that all the molecules show intense fluorescence both in solution and in the aggregated state. In THF solutions, a blue emission was observed for the unsubstituted (H), methyl- (Me) and tert-butyl- (t-Bu) substituted γ-diphenylnaphthalonitriles, which can be attributed to a weak π-donor capability of these groups. On the other hand, the methoxy- (OMe), methylsulfanyl- (SMe) and dimethylamino- (NMe2) substituted compounds exhibit a progressive red-shift in emission compared to H, Me and t-Bu due to a growing π-electron donating capability. Interestingly, upon aggregation in water-containing media, H, Me and t-Bu show a slight red-shift of the emission and a blue-shift is observed for OMe, SMe and NMe2. The crystal structure of Me allowed a detailed discussion of the structure–property relationship. Clearly, N-containing substituents such as NMe2 possess more electron-donating ability than the S-based moieties such as SMe. Moreover, it was found that NMe2 showed higher luminescence quantum yields (ΦF) in comparison to SMe, indicating that N-substituted groups could enhance the fluorescence intensity. Therefore, the π-donor nature of the substituents on the phenyl ring constitutes the main parameter that influences the photophysical properties, such as excited state lifetimes and photoluminescence quantum yields. Hence, a series of highly luminescent materials from deep blue to red emission depending on substitution and environment is reported with potential applications in sensing, bioimaging and optoelectronics.
Keywords: aggregation caused quenching (ACQ); aggregation-induced emission enhancement (AIEE); naphthalonitriles (NCNs); solution and solid state emitters (SSSE); solvent quenching (SQ)

(untitled) - Shimizu, M.; Takeda, Y.; Higashi, M.; Hiyama, T. (Angew. Chem., Int. Ed., 2009)

(untitled) - Chan, C. Y. K.; Zhao, Z.; Lam, J. W. Y.; Liu, J.; Chen, S.; Lu, P.; Mahtab, F.; Chen, X.; Sung, H. H. Y.; Kwok, H. S.; Ma, Y.; Williams, I. D.; et al. (Adv. Funct. Mater., 2012)

(untitled) - Sun, H.; Liu, S.; Lin, W.; Zhang, K. Y.; Lv, W.; Huang, X.; Huo, F.; Yang, H.; Jenkins, G.; Zhao, Q.; Huang, W. (Nat. Commun., 2014)

(untitled) - Luo, J.; Gong, S.; Gu, Y.; Chen, T.; Li, Y.; Zhong, C.; Xie, G.; Yang, C. (J. Mater. Chem. C, 2016)

(untitled) - Ma, Y.; Liang, H.; Zeng, Y.; Yang, H.; Ho, C.-L.; Xu, W.; Zhao, Q.; Huang, W.; Wong, W.-Y. (Chem. Sci., 2016)

(untitled) - Liu, S.; Zhou, N.; Chen, Z.; Wei, H.; Zhu, Y.; Guo, S.; Zhao, Q. (Opt. Lett., 2017)

(untitled) - Shi, H.; Ma, X.; Zhao, Q.; Liu, B.; Qu, Q.; An, Z.; Zhao, Y.; Huang, W. (Adv. Funct. Mater., 2014)

(untitled) - Yang, Z.; Zhao, N.; Sun, Y.; Miao, F.; Liu, Y.; Liu, X.; Zhang, Y.; Ai, W.; Song, G.; Shen, X.; Yu, X.; Sun, J.; et al. (Chem. Commun., 2012)

(untitled) - Anthony, J. E. (Chem. Rev., 2006)

(untitled) - Wen, P.; Gao, Z.; Zhang, R.; Li, A.; Zhang, F.; Li, J.; Xie, J.; Wu, Y.; Wu, M.; Guo, K. (J. Mater. Chem. C, 2017)

(untitled) - Chen, G.; Li, W.; Zhou, T.; Peng, Q.; Zhai, D.; Li, H.; Yuan, W. Z.; Zhang, Y.; Tang, B. Z. (Adv. Mater. (Weinheim, Ger.), 2015)

(untitled) - Iida, A.; Yamaguchi, S. (Chem. Commun., 2009)

(untitled) - Langhals, H.; Krotz, O.; Polborn, K.; Mayer, P. (Angew. Chem., Int. Ed., 2005)

(untitled) - Sun, Y.; Wu, T.; Zhang, F.; Zhang, R.; Wu, M.; Wu, Y.; Liang, X.; Guo, K.; Li, J. (Dyes Pigm., 2018)

(untitled) - Wakamiya, A.; Mori, K.; Yamaguchi, S. (Angew. Chem., Int. Ed., 2007)

(untitled) - Zhao, C.-H.; Wakamiya, A.; Inukai, Y.; Yamaguchi, S. (J. Am. Chem. Soc., 2006)

(untitled) - Xie, Z.; Yang, B.; Li, F.; Cheng, G.; Liu, L.; Yang, G.; Xu, H.; Ye, L.; Hanif, M.; Liu, S.; Ma, D.; Ma, Y. (J. Am. Chem. Soc., 2005)

(untitled) - Kaiser, T. E.; Wang, H.; Stepanenko, V.; Würthner, F. (Angew. Chem., Int. Ed., 2007)

(untitled) - Zhu, X.; Gindre, D.; Mercier, N.; Frère, P.; Nunzi, J.-M. (Adv. Mater. (Weinheim, Ger.), 2003)

(untitled) - Xue, P.; Lu, R.; Chen, G.; Zhang, Y.; Nomoto, H.; Takafuji, M.; Ihara, H. (Chem. – Eur. J., 2007)

(untitled) - An, B.-K.; Kwon, S.-K.; Jung, S.-D.; Park, S. Y. (J. Am. Chem. Soc., 2002)

(untitled) - Guo, K.; Zhang, F.; Guo, S.; Li, K.; Lu, X.; Li, J.; Wang, H.; Cheng, J.; Zhao, Q. (Chem. Commun., 2017)

(untitled) - Luo, J.; Xie, Z.; Lam, J. W. Y.; Cheng, L.; Tang, B. Z.; Chen, H.; Qiu, C.; Kwok, H. S.; Zhan, X.; Liu, Y.; Zhu, D. (Chem. Commun., 2001)

(untitled) - Yu, G.; Yin, S.; Liu, Y.; Chen, J.; Xu, X.; Sun, X.; Ma, D.; Zhan, X.; Peng, Q.; Shuai, Z.; Tang, B.; Zhu, D.; et al. (J. Am. Chem. Soc., 2005)

(untitled) - Han, F.; Zhang, R.; Zhang, Z.; Su, J.; Ni, Z. (RSC Adv., 2016)

(untitled) - Mei, J.; Leung, N. L. C.; Kwok, R. T. K.; Lam, J. W. Y.; Tang, B. Z. (Chem. Rev., 2015)

(untitled) - Mei, J.; Hong, Y.; Lam, J. W. Y.; Qin, A.; Tang, Y.; Tang, B. Z. (Adv. Mater. (Weinheim, Ger.), 2014)

(untitled) - Hong, Y.; Lam, J. W. Y.; Tang, B. Z. (Chem. Commun., 2009)

(untitled) - Wang, M.; Zhang, G.; Zhang, D.; Zhu, D.; Tang, B. Z. (J. Mater. Chem., 2010)

(untitled) - Huang, J.; Jiang, Y.; Yang, J.; Tang, R.; Xie, N.; Li, Q.; Kwok, H. S.; Tang, B. Z.; Li, Z. (J. Mater. Chem. C, 2014)

(untitled) - Guo, K.; Gao, Z.; Cheng, J.; Shao, Y.; Lu, X.; Wang, H. (Dyes Pigm., 2015)

(untitled) - Galer, P.; Korošec, R. C.; Vidmar, M.; Šket, B. (J. Am. Chem. Soc., 2014)

(untitled) - Huang, M.; Zhou, J.; Xu, K.; Zhu, X.; Wan, Y. (Dyes Pigm., 2019)

(untitled) - Riebe, S.; Vallet, C.; van der Vight, F.; Gonzalez-Abradelo, D.; Wölper, C.; Strassert, C. A.; Jansen, G.; Knauer, S.; Voskuhl, J. (Chem. – Eur. J., 2017)

(untitled) - Riebe, S.; Wölper, C.; Balszuweit, J.; Hayduk, M.; Gutierrez Suburu, M. E.; Strassert, C. A.; Doltsinis, N. L.; Voskuhl, J. (ChemPhotoChem, 2020)

(untitled) - del Rey, B.; Keller, U.; Torres, T.; Rojo, G.; Agulló-López, F.; Nonell, S.; Martí, C.; Brasselet, S.; Ledoux, I.; Zyss, J. (J. Am. Chem. Soc., 1998)

(untitled) - Hofman, J.-W.; van Zeeland, F.; Turker, S.; Talsma, H.; Lambrechts, S. A. G.; Sakharov, D. V.; Hennink, W. E.; van Nostrum, C. F. (J. Med. Chem., 2007)

(untitled) - Weber, J.; Beard, P. C.; Bohndiek, S. E. (Nat. Methods, 2016)

(untitled) - Jadhav, T.; Dhokale, B.; Misra, R. (J. Mater. Chem. C, 2015)

(untitled) - Shen, X. Y.; Yuan, W. Z.; Liu, Y.; Zhao, Q.; Lu, P.; Ma, Y.; Williams, I. D.; Qin, A.; Sun, J. Z.; Tang, B. Z. (J. Phys. Chem. C, 2012)

(untitled) - Li, Y.; Li, F.; Zhang, H.; Xie, Z.; Xie, W.; Xu, H.; Li, B.; Shen, F.; Ye, L.; Hanif, M.; Ma, D.; Ma, Y. (Chem. Commun., 2007)

(untitled) - Misra, R.; Jadhav, T.; Dhokale, B.; Mobin, S. M. (Chem. Commun., 2014)

(untitled) - Qiu, Q.; Xu, P.; Zhu, Y.; Yu, J.; Wei, M.; Xi, W.; Feng, H.; Chen, J.; Qian, Z. (Chem. – Eur. J., 2019)

(untitled) - Situ, B.; Chen, S.; Zhao, E.; Leung, C. W. T.; Chen, Y.; Hong, Y.; Lam, J. W. Y.; Wen, Z.; Liu, W.; Zhang, W.; Zheng, L.; Tang, B. Z. (Adv. Funct. Mater., 2016)

(untitled) - Dubinina, T. V.; Ivanov, A. V.; Borisova, N. E.; Trashin, S. A.; Gurskiy, S. I.; Tomilova, L. G.; Zefirov, N. S. (Inorg. Chim. Acta, 2010)

(untitled) - Dubinina, T. V.; Trashin, S. A.; Borisova, N. E.; Boginskaya, I. A.; Tomilova, L. G.; Zefirov, N. S. (Dyes Pigm., 2012)

(untitled) - Song, C. J.; Jang, C. K.; Yao, W.; Jaung, J. Y. (J. Chem. Res., 2013)

(untitled) - Dubinina, T. V.; Borisova, N. E.; Paramonova, K. V.; Tomilova, L. G. (Mendeleev Commun., 2011)

(untitled) - Ramírez, M. A.; Cuadro, A. M.; Alvarez-Builla, J.; Castaño, O.; Andrés, J. L.; Mendicuti, F.; Clays, K.; Asselberghs, I.; Vaquero, J. J. (Org. Biomol. Chem., 2012)

(untitled) - Kulhánek, J.; Bureš, F. (Beilstein J. Org. Chem., 2012)

(untitled) - Zhu, J.; Lu, C.; Cui, Y.; Zhang, C.; Lu, G. (J. Chem. Phys., 2010)

(untitled) - Dokládalová, L.; Bureš, F.; Kuznik, W.; Kityk, I. V.; Wojciechowski, A.; Mikysek, T.; Almonasy, N.; Ramaiyan, M.; Padělková, Z.; Kulhánek, J.; Ludwig, M. (Org. Biomol. Chem., 2014)